2010
DOI: 10.1111/j.1750-3841.2010.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characterization of Celery (Apium graveolens L.) by Plant Zones and Two Harvest Dates

Abstract: The aim of this study was to characterize the quality of celery petioles (Apium graveolens L. cv Golden Clause) from the external, middle, and internal zones of each plant. Harvest dates were 93 (HD1) and 124 (HD2) days after transplantation. Total weight (TW), total length (TL), total leaves number (LN), and petiole length of leaves (PL) for the 3 zones were measured. Physicochemical (color, b* and h; texture; total soluble solids, TSS; titratable acidity, TA; water content, WC), nutraceutical (ascorbic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Goñi et al (2010) and Agüero et al (2011) also found lower values of AA in inner leaves of butterhead lettuce. However, Guerra et al (2010), working with celery, reported that undeveloped inner leaves presented the highest AA content. This discrepancy may be due to the different vegetable crop used in the studies as well as differences in growth habit and growing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Goñi et al (2010) and Agüero et al (2011) also found lower values of AA in inner leaves of butterhead lettuce. However, Guerra et al (2010), working with celery, reported that undeveloped inner leaves presented the highest AA content. This discrepancy may be due to the different vegetable crop used in the studies as well as differences in growth habit and growing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Harvesting of celery (leafy or turnip-rooted types) is carried out manually, especially when successive harvesting is implemented, or mechanically for large fields when the product is meant for industrial purposes. Although the harvesting date is genotype and growing conditions dependent, early harvests may improve the quality of the end product mostly through the visual appearance (color and texture) and physicochemical composition [80], as well as through the increased content of essential oil in the leaves [81]. Late harvests may increase total yield when a single harvest is implemented, however the overall quality of celery petioles is reduced, especially in terms of tissue texture [82].…”
Section: Harvestingmentioning
confidence: 99%
“…Differences in RWC between inner (younger) and outer leaves (older) could be attributed to metabolic differences instead of different exposure level to environmental conditions. Guerra et al [24] found similar results for greenhouse celery (Apium graveolens L.), attributing differences to degree of tissue development.…”
Section: Quality Indices Distribution In Freshly Harvested Lettucementioning
confidence: 60%